A superjunction structure using high-k insulator for power devices: theory and optimization*Project supported by the National Natural Science Foundation of China (No. 51237001). (June 2016) - Mingmin 黄, Huang 铭敏; Xingbi 陈, Chen 星弼
Abstract: A superjunction (SJ) structure using a high- k (H k ) insulator is studied and optimized by using an analytic model. Results by using the proposed model match well with that of numerical calculations. Numerical calculation results show that, only needing an H k insulator with a permittivity of ϵI = 5ϵS, the optimum specific on-resistance of the MOSFET applying the proposed structure is about 8%–20% lower than that of the conventional SJ-MOSFET with V B = 200–1000 V. An example with V B = 400 V shows that, the permissible error range of doping concentration of the p-region to maintain above 80% of V B is from −37% to +32% for the former and is only from −13% to +13% for the latter.